RESEARCH OF POWER GENERATOR PROTOTYPE DEVELOPMENT AND INTEGRATION INTO AUTONOMOUS ROBOTIC SYSTEMS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The aim of the research is to perform experimental research based on patented technology to study the efficiency and applicability of it in the power supply circuits of autonomous robotic systems. Ensuring longer autonomous operation of the robotic system, was chosen electric car as the object of practical application at this stage of investigations to improve a process generation, utilization and regeneration of electricity. The article reviews the difficulties of technologies and aspects of their practical application. Described research methodology and a stand of investigations. Presented the results and conclusions of the performed simulation tests and practical measurements of the prototype electrodynamic parameters.